Speed choice and speeding behavior on Indonesian highways: Extending the theory of planned behavior - Hanif Qaid; Ari Widyanti; Sheila Amalia Salma; Fitri Trapsilawati; Titis Wijayanto; Utami Dyah Syafitri; Nur Chamidah (IATSS Research, 2022)
Objective: Speeding has been reported as a major cause of highway accidents. The purpose of this study was to observe the speed choice and speeding intention of Indonesian drivers using the theory of planned behavior (TPB), legal sanctions, and Homel's model. Methods: Five hundred Indonesian driver respondents with experience crossing Indonesian highways voluntarily participated in this study (mean age = 40.48 years, Stdev = 12.59 years; 355 male, 145 female). A self-administered questionnaire including demographic characteristics and a questionnaire based on the construct of the TPB, legal sanctions, and Homel's model were used to collect data. Descriptive statistics were applied to present demographic data and speeding behavior. Structural equation modeling was then used to model speeding intention. Results: The average speed of Indonesian drivers on highways was 90.1 km/h. The demographic data of respondents indicated that speeding behavior differs based on occupation, with non-government employees speeding more than other occupations. Conclusion: The model shows that speed intention is directly influenced by cognitive attitude, affective attitude, and non-legal sanctions.